ANALISIS PENGARUH KESEHATAN KERJA,LINGKUNGAN KERJA DAN DISIPLIN TERHADAP PRODUKTIVITAS KARYAWAN DI PT CIPTA ADIL INDUSTRIES BATAM - Yurisman, Yurisman Zendrato; Saputra, Asron (SCIENTIA JOURNAL, 2021)
In today's business competition, it is very tight, caused by advances in human knowledge about the use of technology in business activities which greatly helps speed in doing business. Of course, in this case, business people or business people really need human resources who have the ability to use the current digital era, to launch the business he runs. Apart from human resources, of course, a businessman needs other resources such as capital, materials and other supporting tools such as machines to support the smooth operation of a business or business. In this study, he conducted research related to human resources. owned to analyze theeffect of occupational health, work environment and discipline on employee productivity at PT Cipta Adil Industries Batam, a company engaged in the manufacture of plastic ore. Researchers conducted an analysis of 130 respondents who were employees of PT Ci PTA Adil Industries Batam by using quantitative research methods. Researchers use simple saturation techniques in determining the sample. Variables are measured using a Likert scale and translated into research indicators. On a Likert scale, the answers in the form of statements have been determined by researchers ranging from positive to negative. The data obtained were analyzed using SPSS 25. The results showed that occupational health had a significant effect on employee productivity as evidenced by a significance value of 0.004 <0.05. The work environment has a significant effect on employee productivity as evidenced by a significance value of 0.007> 0.05. And discipline has a positive and significant effect on employee productivity as evidenced by a significant value of 0.000> 0.05. The test results show an R Squer value of 697 or 69.7 % employee productivity can be explained by occupational health, work environment and discipline. The remaining 31.3% is not explained in this study. So the researcher concludes that occupational health has no effect on employee productivity and two other variables, namely the work environment and variables affect productivity.